Perilaku Remaja Tentang Pencegahan Sanitasi Lingkungan Pada Penyakit Skabies Di Pondok Pesantren - Amelia Dini Angraini Silalahi; Sri Legawati; Joni Siagian; R. Sri Rezeki; Efi Irwansyah Pane; Yuriansah; M. Arif Simangunsong; Sri Julita (LPPM AKPER GITA MATURA ABADI KISARAN, 2026)
Scabies is a skin disease endemic to tropical and subtropical regions, caused by infestation and sensitization by the Sarcoptes scabies mite. Its primary symptom is nocturnal itching that disrupts daily activities and productivity. Scabies has the potential to spread rapidly within communities such as Islamic boarding schools particularly where sanitation is inadequate. This study aimed to improve understanding and provide education regarding adolescent behaviors concerning environmental sanitation for scabies prevention at the Bina Ulama Asahan Islamic boarding school. A quantitative descriptive survey design was employed, with a sample of 79 individuals selected from the total population using simple random sampling. The results revealed that the majority of respondents (54 individuals or 70.9%) possessed a good level of knowledge regarding environmental sanitation for scabies prevention. Similarly, the majority of respondents (56 individuals or 68.4%) demonstrated a positive attitude toward environmental sanitation for scabies prevention. Continuous educational reinforcement is necessary to ensure that this positive knowledge and attitude regarding scabies prevention are fully applied in daily life, given that the environment of Islamic boarding schools possesses characteristics conducive to scabies transmission in the absence of adequate preventive measures.